ANALISIS KESEJAHTERAAN PEDAGANG KAKI LIMA DI KOTA SIGLI KABUPATEN PIDIE - Rizki Saputra; Eddy Gunawan (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2019)
AbstractThe purpose of this study was to determine the level of welfare of street vendors in Sigli City before with after market relocation. The population in this study were all street vendors, totaling 166 street vendors. Sampling is done using the "Census" method. Census method is a method used to examine all the elements in the research area so that the results of the study will be more realistic. To find out the level of welfare of street vendors in the City of Sigli seen from the income obtained by traders before the after market relocation using a different test (t test ) This identified that there had been a decline in the level of welfare of street vendors in the city of Sigli Post-Relocation of their place of sale by the Pidie Government. The decline in street vendors' income after relocation reached almost 50 percent of the previous sales points. The results of verification using a different test show that the count of the output is 87.716 greater than the t table of 2.0086. Ha in this study accepted means that the average income of street vendors before relocation with after market relocation is different.Keywords: Street, Vendors and welfare